2017
DOI: 10.1155/2017/4737082
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Rhythm of Copeptin, the C-Terminal Portion of Arginine Vasopressin

Abstract: Background Several studies have investigated copeptin as a prognostic marker of different acute diseases and as a diagnostic marker in disorders of water and salt homeostasis. However, no data of the normal circadian rhythm of copeptin in healthy subjects are available. Aim To investigate the circadian rhythm of copeptin in healthy subjects under standardized conditions. Methods 19 healthy volunteers aged 18 to 53 years, male and female, were studied in a prospective observational study. In all 19 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…While copeptin levels show no significant variation in response to circadian rhythm or digestion, levels significantly decreased from 4.9 to 3.2 pmol/L after oral fluid intake of as little as 200‐300 mL, which has to be considered for interpretation of values in clinical practice.…”
Section: Copeptinmentioning
confidence: 99%
“…While copeptin levels show no significant variation in response to circadian rhythm or digestion, levels significantly decreased from 4.9 to 3.2 pmol/L after oral fluid intake of as little as 200‐300 mL, which has to be considered for interpretation of values in clinical practice.…”
Section: Copeptinmentioning
confidence: 99%
“…The correlation among AVP levels, serum osmolality and copeptin values is actually well known . In adults, copeptin circadian rhythm is similar to the AVP rhythm, but both peaks and nadirs are delayed, likely for the copeptin longer half‐time (86 minutes vs 44 minutes); this rhythm seems to be slightly blunted in nocturnal polyuria .…”
Section: Introductionmentioning
confidence: 97%
“…The correlation among AVP levels, serum osmolality and copeptin values is actually well known . In adults, copeptin circadian rhythm is similar to the AVP rhythm, but both peaks and nadirs are delayed, likely for the copeptin longer half‐time (86 minutes vs 44 minutes); this rhythm seems to be slightly blunted in nocturnal polyuria . Recent studies in the paediatric age have explored the possibility to utilize copeptin also as a high‐risk marker for community‐acquired pulmonitis, septic shock, stroke and head trauma; in these studies, copeptin values in the control population were reported between 2.4 and 8.6 pmol/L …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have evaluated the usefulness of plasma copeptin in the differential diagnosis of hyponatremic and hypernatremic AVP-related disorders, as it represents a stable and rapidly available surrogate of plasma AVP [32][33][34]. It has proven to be very useful in the distinction of hypernatremic conditions (such as CDI, NDI, and PP) and less useful in hyponatremia due to the important overlap between SIADH, hyper-or hypovolemic hyponatremia [35][36][37][38][39][40][41][42][43][44][45][46][47], a finding already reported also in a small number of pediatric patients [42].…”
Section: Introductionmentioning
confidence: 99%